Mobile sourcing: A case study of journalistic norms and usage of chat apps. (January 2018) - Belair-Gagnon, Valerie; Agur, Colin; Frisch, Nicholas
Since 2011, mobile chat apps have gained significant popularity worldwide and the leading chat apps have surpassed social networking sites in user numbers. These apps have become the hosts for everyday communication among a wide variety of users and, thanks to the functionalities of certain apps, have taken on new significance in reporting. Especially in Hong Kong (a high-income, high-tech society in which smartphones are in widespread use) and mainland China (an emerging market with more than 1 billion mobile phone users), journalists have turned to these apps to complement face-to-face interactions to gather news. Drawing on a case study building on in-depth interviews with foreign correspondents based in China and Hong Kong, this article discusses how journalists use chat apps and establish trust with their sources. This article explores journalistic sourcing on apps (e.g., encrypted or not encrypted; open or one-to-one communication), and seeks to understand individual and systemic levels of trust. It finds that there are differences of trust depending on the functionalities of individual chat apps, and that interactions in journalistic sourcing in face-to-face and online environments affect the generation and output of news stories. Chat apps allow reporters to use open or closed networks, and adopt one of several approaches: trust the network, master the network, or abandon the network. These findings suggest that chat apps have an important role in communicating with sources, and should be a part of efforts to theorize journalistic sourcing.